Response to the Respondents: Competition, Qumran and Supersessionism - Marcus, Joel (Journal for the study of the historical Jesus, 2021)
The critics of JBHT in this issue have questioned three main aspects of the book: its assertion that early Christians competed with people who believed that John the Baptist was the principal figure in the history of salvation, its assertion that early in his career the Baptist was a member of the Qumran community, and the way in which the book situates the Baptist in relation to Second Temple Judaism in general. The article addresses these concerns, rebutting certain objections but acknowledging areas in which the book could have been more nuanced or further developed.